Modeling of continuous adsorption of greywater pollutants onto sawdust activated carbon bed integrated with sand column. Issue 2 (April 2022) - Patel, Pushpraj; Gupta, Shubhi; Mondal, Prasenjit
Abstract: The real greywater samples collected from the IIT Roorkee hostel have been treated using waste biomass-derived activated carbon in continuous operation. The synthesized ZnCl2 impregnated sawdust activated carbon (SAC) has been used to remove the COD, BOD, and TDS concentration from the greywater. The SAC characterization through FESEM-EDX, BET, and FTIR has been performed. The initial concentration of COD, BOD, and TDS in greywater was 670, 275, and 1819.52 mg/L, respectively. The sand column was used to retain the larger suspended solids and dissolved organic matter up to a certain concentration. Sand column effluent with the concentration of 412, 180, and 1116.8 mg/L for COD, BOD, and TDS respectively, was drawn to the adsorption column for studying the influence of flow rate (5, 10, and 15 mL/min) at 15 cm of bed height and the effect of bed height (10 and 20 cm) at 10 mL/min of flow rate. At optimum condition of 10 mL/min flow rate and 10 cm of bed height, the observed adsorption capacities are 3904.62, 1967.3, and 14, 936.92 mg/g for the removal of COD, BOD, and TDS, respectively. Further, to comprehend the behavior of the breakthrough curves eight mathematical models, namely, Bohart-Adams, Thomas, Wolborska, Yoon-Nelson, Log Gompertz, Gompertz, Dose-Response, and Bed Depth Service Time (BDST), have been tested. Graphical Abstract: ga1 Highlights: Composite greywater sample collected from Institute hostel. ZnCl2 impregnated sawdust activated carbon has been synthesized. Conducted continuous adsorption study at different experimental conditions. Experimental data were validated with eight mathematical models. Integration of sand column to increase the efficacy of the column.